Homo Educandum and Homo Viator: Embracing nature as Eschatological community - Pantan, Frans (Verbum et ecclesia, 2025)
Modernisation and globalisation threaten the sustainability of traditions and local wisdom of the Tengger community, especially in their relationship with nature. Christian education, which has so far focused on the themes of salvation and eschatology, often ignores ecological issues. This article integrates the concepts of Homo Educandum and Homo Viator as philosophical approaches in ecological Pentecostal Christian education. The Lurung Kasada tradition in Tengger is used as a case study to emphasise the importance of spiritual relations between humans and nature. Through education based on experience and local wisdom, the younger generation is invited to understand nature as part of the eschatological community. Holistic Pentecostal Christian education can build ecological awareness of the younger generation and strengthen cross-cultural and spiritual relationships. Thus, this article offers a new paradigm in theological education that is relevant to global ecological challenges, rooted in local culture and enriches the perspective of Christian eschatology. Intradisciplinary and/or interdisciplinary implications: This article connects Christian ecotheology with local cultural and philosophical studies to enrich local wisdom-based theological education. This concept offers a new approach to responding to the global ecological crisis.